2018
DOI: 10.1007/s12035-017-0851-5
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Biased Expression of the CNTN6 Gene in iPS Cell-Derived Neurons from a Patient with Intellectual Disability and 3p26.3 Microduplication Involving the CNTN6 Gene

Abstract: Copy number variations (CNVs) of the human CNTN6 gene caused by megabase-scale microdeletions or microduplications in the 3p26.3 region are often the cause of neurodevelopmental disorders, including intellectual disability and developmental delay. Surprisingly, patients with different copy numbers of this gene display notable overlapping of neuropsychiatric symptoms. The complexity of the study of human neuropathologies is associated with the inaccessibility of brain material. This problem can be overcome thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Currently, both experimental data describing 3D-genome alterations for known rearrangements and tools modeling spatial landscape of novel variants are limited. In the same time, others 20,21,29,30 and we 31 have recently reported novel variations with unexpected pathological phenotype, which might be explained, at least partially, by changes of chromatin organization 32,33 . Future development and validation of models predicting chromatin contacts in rearranged genome is essential for better understanding of biomedical consequences of these rearrangements.…”
Section: Discussionsupporting
confidence: 50%
“…Currently, both experimental data describing 3D-genome alterations for known rearrangements and tools modeling spatial landscape of novel variants are limited. In the same time, others 20,21,29,30 and we 31 have recently reported novel variations with unexpected pathological phenotype, which might be explained, at least partially, by changes of chromatin organization 32,33 . Future development and validation of models predicting chromatin contacts in rearranged genome is essential for better understanding of biomedical consequences of these rearrangements.…”
Section: Discussionsupporting
confidence: 50%
“…Among these founders, we identified two mosaic animals carrying a 2,274 kb duplication involving the same gene. These mice may be useful experimental models for neurodevelopmental disorders since they contain similar chromosomal rearrangements affecting the CNTN6 gene in human 2629 . For this reason, it is important to estimate level of unpredicted DNA changes accompanying the rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, both the experimental data describing 3D genome alterations associated with known rearrangements and tools modeling the spatial landscape of novel variants are limited. At the same time, we (Gridina et al 2018) and others (Lupiáñez et al 2015;Franke et al 2016;Redin et al 2017;Zepeda-Mendoza et al 2017) have recently reported novel variations with unexpected pathological phenotypes, which might be explained, at least partially, by changes of chromatin organization (Fishman et al 2018;Spielmann et al 2018). Future development and validation of models predicting chromatin contacts in a rearranged genome is essential for a better understanding of the biological consequences of these rearrangements.…”
Section: Discussionmentioning
confidence: 67%